2013
DOI: 10.1111/iju.12358
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical hyaluronidase causes chronic cystitis in a rat model: A potential model of bladder pain syndrome/interstitial cystitis

Abstract: Abbreviations & Acronyms BC = bladder capacity BP = base pressure BPS = bladder pain syndrome BW-A = bodyweight after instillation BW-B = bodyweight before instillation CMG = cystometry CYP = cyclophosphamide GAG = glycosaminoglycan GAPDH = glyceraldehydes-3-phosphate dehydrogenase HA = hyaluronic acid HAase = hyaluronidase HHAase = high-dose hyaluronidase IC = interstitial cystitis ICAM-1 = intercellular adhesion molecule-1 ICI = intercontraction intervals IL = interleukin LHAase = low-dose hyaluronidase mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Intravesical bladder immunotherapy with BCG or Ty21a is associated with the induction of inflammatory cytokines (7,17). Here, we show a morphological analysis of treated bladders to characterize inflammatory features, including the presence of edema, fibrosis, and immune cell infiltration, as summarized by an inflammatory score (11) (Fig. 1A).…”
Section: Characterization Of Bladder Wall Inflammation Upon Intravesimentioning
confidence: 80%
See 1 more Smart Citation
“…Intravesical bladder immunotherapy with BCG or Ty21a is associated with the induction of inflammatory cytokines (7,17). Here, we show a morphological analysis of treated bladders to characterize inflammatory features, including the presence of edema, fibrosis, and immune cell infiltration, as summarized by an inflammatory score (11) (Fig. 1A).…”
Section: Characterization Of Bladder Wall Inflammation Upon Intravesimentioning
confidence: 80%
“…Three m paraffin embedded Hematoxilin-eosin stained sections were used for morphological evaluation of bladder specimens, including the urothelial mucosa, muscular, subserosa, and serosa layers. The inflammation was evaluated using an inflammatory scoring system as previously reported (11). Score 0: absence or minimal inflammation or epithelial changes.…”
Section: Morphology and Immunohistochemistrymentioning
confidence: 99%
“…The breakdown products of hyaluronan, known as low molecular hyaluronan, have both pro-inflammatory and pro-oncogenic effects [ 35 ]. Studies in rats showed that intravesical injection of hyaluronidase resulted in inflammation and an increase in the number of activated mast cells, suggesting a direct role between hyaluronan break down products and mast cell activation and migration [ 36 , 37 ]. In vitro studies have also shown that mast cell proliferation can be inhibited by hyaluronan excreted by co-cultured cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As urothelial irritation is considered one of the etiopathogenic factors of cystitis, one way to reduce irritation is physical protection of the urothelium against irritating substances of urine . Long‐chain polysaccharides such as HA and pentosan polysulfate sodium have been shown to reduce experimentally induced bladder inflammation and also hyperactivity by physically protecting the GAG layer. Another way to improve bladder function could be modulation of the immune system.…”
Section: Discussionmentioning
confidence: 99%